Comparison of whole‐blood tacrolimus concentrations measured by different immunoassay systems. Issue 9 (5th July 2018) - Kaneko, Tetsuya; Fujioka, Takashi; Suzuki, Yosuke; Nagano, Toshiaki; Sato, Yuhki; Asakura, Syunji; Itoh, Hiroki
Abstract : Introduction: Different measured values for tacrolimus were obtained with different automated immunoassays. We aimed to examine the differences in the blood tacrolimus concentrations measured by the major immunoassay systems commercially available in Japan. Methods: Whole‐blood samples from 118 patients were assayed by 3 commercial assays: chemiluminescent enzyme immunoassay (CLIA), affinity column‐mediated immunoassay (ACMIA), and enzyme‐multiplied immunoassay technique (EMIT). Liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) was used for reference. Key findings: The correlation coefficient of immunoassay vs LC‐MS/MS was excellent for ACMIA (.83) and CLIA (.81) and good for EMIT (.71). The mean error was negative for ACMIA and positive for CLIA and EMIT. The mean absolute error and root‐mean‐square error were almost the same for ACMIA and CLIA and lower than those for EMIT. Conclusions: The ACMIA and CLIA yield considerably better results than the EMIT for monitoring blood tacrolimus concentrations.